Influence of Altered Knee Angle on Electromyographic Activity of Hamstring Muscles Between Nordic Hamstring Exercise and Nordic Hamstring Exercise with Incline Slope Lower Leg Board - Taspol Keerasomboon; Toshiaki Soga; Norikazu Hirose (International Journal of Sports Physical Therapy, 2022)
# Background